Metal organic framework composite material loaded with nano silicon dioxide as well as preparation method and application of metal organic framework composite material
By loading nanosilicon dioxide in MOF materials and using ellagic acid as an organic ligand, the problems of complex experimental conditions and uncontrollable chemical stability in the functional modification process of existing MOF materials are solved, and the acidic environment is achieved The high-efficiency adsorption effect of high-valent metal ions.
Patent Information
- Application Number
- CN202411480934.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-07
AI Technical Summary
During the functional modification process, the experimental conditions of existing MOF materials are complex, the synthesis is difficult, and the chemical stability is uncontrollable, making it difficult to effectively adsorb and remove radionuclides.
Develop a metal-organic frame composite material with nanosilicon dioxide loading, which improves adsorption performance by loading nanosilicon dioxide in zirconium-organic frame materials using its high oxygen bonds and oxygen-containing adsorption sites, and uses ellagic acid as Organic ligands improve chemical stability.
In an acidic environment, composite materials exhibit high adsorption capacity to high-valent metal ions, especially to thorium ions, and are non-toxic and harmless, easy to separate and recover, and will not cause secondary pollution to the natural environment.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure HDA0005099192130000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a metal organic framework composite material loaded with nano-silicon dioxide, and a preparation method and application thereof. Background Art
[0002] Metal-organic frameworks (MOFs) are crystalline hybrid materials that combine inorganic rigidity with organic flexibility. MOFs have high surface area, porosity, customizable structures, and are easy to synthesize. These properties also make this type of material ideal for applications in the adsorption and removal of radionuclides, for example, it has great potential in extracting metal ions including actinides.
[0003] Recently, some studies have been conducted on the functionalization of MOFs to improve their adsorption capacity. Guo et al. reported a novel quadruple interpenetrating metal-organic framework (MOF) that was constructed by O - The activated samples showed high adsorption selectivity for Th(IV) ions (K d =3.16×10 5 mL g -1 ) and excellent saturation adsorption capacity (165.61 mg g -1 Gumber et al. synthesized an amino-functionalized MOF adsorbent (CAU-1-NH 2 ), according to the form of Th(IV) ions under different pH conditions, it was observed that pH = 5 is an ideal adsorption environment. The adsorption mechanism of Th after adsorption was studied by FT-IR and XPS, which confirmed that Th is chelated with -NH 2 / -OH functional groups for chemical reactions.
[0004] In order to obtain more MOF materials that can be used as adsorbents for radioactive metal ions, different metal organic framework materials can be modified. However, the experimental conditions for functionalization of different MOF materials are different. Functionalization of a new MOF material usually requires re-exploring the experimental conditions, and the synthesis is difficult. In addition, the chemical stability of the functionalized MOF material is uncontrollable. In contrast, the synthesis and preparation of composite materials are simple, and the chemical stability and adsorption performance of the composite materials can be predictably regulated by changing the proportion of the load. Therefore, it is very necessary to develop a MOF composite adsorbent with the ability to efficiently adsorb and remove radionuclides. Summary of the invention
[0005] In view of this, the main purpose of the present invention is to provide a MOF composite material, which has a good adsorption effect on metal ions in an acidic environment.
[0006] To this end, the first aspect of the present invention provides a metal organic framework composite material loaded with nano-silica, wherein the metal organic framework composite material loaded with nano-silica comprises a zirconium-organic framework material and an active component; the active component comprises nano-silica; and the organic ligand of the zirconium-organic framework material is ellagic acid.
[0007] In some embodiments, based on the total weight of the metal-organic framework composite material loaded with nano-silica, the mass fraction of the nano-silica active component is 1.2%-3.0%.
[0008] In some embodiments, the content of the organic ligand is 60%-68% based on the total weight of the zirconium-organic framework material.
[0009] The second aspect of the present application also provides a use of the metal-organic framework composite material loaded with nano-silica described in the first aspect of the present application in adsorbing high-valent metal ions, wherein the high-valent metal ions are selected from metal ions with a valence of +4 or above; preferably, the high-valent metal ions are thorium ions.
[0010] In some embodiments, the use comprises the following steps: mixing the metal-organic framework composite material loaded with nano-silica with a liquid to be treated containing high-valent metal ions.
[0011] In some embodiments, the pH of the liquid to be treated containing high-valent metal ions is less than or equal to 3.
[0012] In some embodiments, the concentration of the high-valent metal ions in the liquid to be treated containing the high-valent metal ions is 15 mg / L-300 mg / L.
[0013] In some embodiments, the adsorption conditions include: temperature of 25-30° C.; shaking rate of 200 r / min-220 r / min; and shaking time of 5-8 h.
[0014] The third aspect of the present application also provides a method for preparing a metal-organic framework composite material loaded with nano-silica, the method comprising uniformly dispersing nano-silica, a metal precursor, an organic ligand, N,N-dimethylformamide, deionized water and an acetic acid solution to obtain a reaction solution, subjecting the reaction solution to a hydrothermal reaction at 140°C-160°C for 8h-10h, filtering and collecting a precipitate, and drying the precipitate to obtain the metal-organic framework composite material loaded with nano-silica; the metal precursor is zirconium (IV) oxychloride octahydrate; and the organic ligand is ellagic acid.
[0015] In some embodiments, the mass ratio of the nano-silicon dioxide to the metal precursor is 0.03-0.08:1.
[0016] In some embodiments, the molar ratio of the organic ligand to the metal precursor is 1.5 to 2.5:1; preferably, the molar ratio of the organic ligand to the metal precursor is 1.9 to 2.1:1.
[0017] In some embodiments, the concentration of the acetic acid solution is 14 to 18 mol L -1 .
[0018] In some embodiments, the volume ratio of N,N-dimethylformamide, acetic acid solution and deionized water is (3-6): (2-4): (1-2); preferably (4-5): (2.5-3.5): (1.5-2).
[0019] In some embodiments, the nano-silicon dioxide is a nano-powder with a particle size of 10-20 nm and a purity of more than 99.5%.
[0020] The nano-silica-loaded metal organic framework composite material of the present invention is used as a radionuclide adsorbent, and has a high adsorption capacity for high-valent metal ions in a solution under acidic conditions, especially under low pH conditions, and the composite material of the present invention is non-toxic and harmless, easy to separate and recycle, and can be reused without causing secondary pollution to the natural environment. The preparation method of the nano-silica-loaded metal organic framework composite material of the present invention only needs to be carried out at normal pressure in an air environment, and the reaction time is short, the method is simple, the raw materials used in the reaction are easy to obtain and low in cost, and has good economic benefits and practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The metal organic framework composite material (SU-102(Zr)@SiO 2 -1)'s X-ray crystal diffraction pattern.
[0022] Figure 2 The metal organic framework composite material (SU-102(Zr)@SiO 2 -2)'s X-ray crystal diffraction pattern.
[0023] Figure 3 This is the X-ray crystal diffraction pattern of the metal organic framework material (SU-102(Zr)) of Comparative Example 1.
[0024] Figure 4 The metal organic framework composite material (SU-102(Zr)@SiO 2 )'s X-ray crystal diffraction pattern.
[0025] Figure 5 The metal organic framework composite material (SU-102(Zr)@SiO 2 -1) Standard adsorption curve for thorium ions. DETAILED DESCRIPTION
[0026] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0028] It should be noted that, in the embodiments of the present invention, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a method or device including a series of elements includes not only the elements explicitly stated, but also other elements not explicitly listed, or also includes elements inherent to the implementation of the method or device. In the absence of further restrictions, an element defined by the sentence "includes a ..." does not exclude the existence of other related elements in the method or device including the element.
[0029] It should be noted that the terms "first\second\third" involved in the embodiments of the present invention are only used to distinguish similar objects, and do not represent a specific order for the objects. It is understandable that the specific order or sequence of "first\second\third" can be interchanged where permitted. It should be understood that the objects distinguished by "first\second\third" can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein.
[0030] Using a single metal-organic framework material as a radioactive metal ion adsorbent can only use the adsorption sites on its organic framework to adsorb metal ions, and the adsorption capacity cannot be adjusted. Functional modification of metal-organic framework materials requires complex experimental conditions, and the adsorption performance of functionalized metal-organic framework materials on metal ions is uncontrollable.
[0031] In view of this, the first aspect of the present invention provides a metal-organic framework composite material loaded with nano-silica, wherein the metal-organic framework composite material loaded with nano-silica comprises a zirconium-organic framework material and an active component; the active component comprises nano-silica; and the organic ligand of the zirconium-organic framework material is ellagic acid.
[0032] In the present invention, the organic ligand of the zirconium-organic framework material is ellagic acid, which has better chemical stability and can provide more oxygen adsorption sites. Nano-silicon dioxide, as an active component, has more oxygen-containing adsorption sites such as silicon-oxygen bonds and high oxygen bonds, and has good adsorption performance for metal ions; on the other hand, nano-silicon dioxide is also beneficial to improving the chemical stability of MOF materials. By loading nano-silicon dioxide on the zirconium-organic framework material, the adsorption sites of the active component nano-silicon dioxide can be enriched, and the adsorption performance of the composite material can be further improved; in addition, the composite material loaded with nano-silicon dioxide has a stable structure and can improve the service life of the material.
[0033] The composite material provided by the present invention can be used as an adsorbent for adsorbing high-valent metal ions, adsorbing and recovering metal ions from solutions, and exhibits a high adsorption capacity for high-valent metal ions, especially thorium ions. In addition, the composite material of the present invention is non-toxic and harmless, easy to separate and recover, and can be reused without causing secondary pollution to the natural environment. It has good application prospects in the adsorption and recovery of radioactive nuclides.
[0034] In some embodiments, the mass fraction of the active component is 1.2%-3.0% based on the total weight of the metal organic framework composite material loaded with nano-silica. In the present invention, the mass fraction of the active component and the mass fraction of the zirconium-organic framework material are calculated by the mass ratio of the raw materials in the material preparation process. By making the mass fraction of the active component within the above range, it is beneficial to fully and synergistically utilize the oxygen adsorption sites in the nano-silica and the oxygen adsorption sites of the metal organic framework itself, thereby improving the adsorption performance of the metal organic framework composite material loaded with nano-silica. Exemplarily, based on the total weight of the metal organic framework composite material loaded with nano-silica, the mass fraction of the active component can be 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0% or a value between the ranges composed of any two of them.
[0035] In some embodiments, the mass fraction of the organic ligand is 60%-68% based on the total weight of the zirconium-organic framework material. In the present invention, the mass fraction of the organic ligand is calculated by the mass ratio of the raw materials in the material preparation process. By making the mass fraction of the organic ligand within the above range, it is beneficial to improve the crystallinity of the metal organic framework material, thereby improving the chemical stability of the composite material. Exemplarily, based on the total weight of the zirconium-organic framework material, the mass fraction of the organic ligand can be 60%, 62%, 64%, 66%, 68% or a value between the ranges consisting of any two of them.
[0036] The second aspect of the present invention further provides a use of the metal organic framework composite material loaded with nano-silica as described in the first aspect of the present invention in adsorbing high-valent metal ions, wherein the high-valent metal ions are selected from metal ions with a valence of +4 or more; preferably, the high-valent metal ions are thorium ions. In the metal organic framework composite material loaded with nano-silica of the present invention, the nano-silica active component has oxygen-containing adsorption sites, which are electronegative and absorb high-valent metal ions, especially metal ions with a valence of +4 or more, such as Th. 4+ ; Ce 4 + , U 4+ , Pu 4+ 、Np 4+ The metal organic framework composite material loaded with nano-silicon dioxide has a good adsorption effect on thorium ions.
[0037] In some embodiments, the use comprises the following steps: mixing the nano-silica loaded metal organic framework composite material with a liquid to be treated containing high-valent metal ions. The composite material of the present invention is easy to use and can achieve adsorption of high-valent metal ions by mixing the nano-silica loaded metal organic framework composite material of the present invention with a liquid to be treated containing high-valent metal ions, and has good application prospects in the adsorption and removal of radioactive nuclides.
[0038] In some embodiments, the pH of the liquid to be treated containing high-valent metal ions is less than or equal to 3. The inventors have found that when the pH of the liquid to be treated containing high-valent metal ions is within the above range, the metal ions in the liquid to be treated, especially the thorium ions, exist in the form of ions, and can be combined with the metal-organic framework composite material loaded with nano-silicon dioxide of the present invention at least through electrostatic action. Further, the thorium ions are combined with the oxygen adsorption sites in the silicon dioxide and the metal-organic framework. The thorium ions can not only interact with the surface of the composite material through electrostatic interaction, but also complex with more oxygen-containing binding sites, which is conducive to the composite material of the present invention to achieve good adsorption. When the pH is greater than 3, high-valent metal ions, such as thorium ions, exist in the form of hydrates of thorium ions in aqueous solution, wherein the thorium ions are wrapped by numerous hydroxide ions, thereby forming a variety of different forms of thorium hydroxide hydrate ions (such as Th(OH) 3+ 、Th(OH) 2 2+ ,Th 2 (OH) 3 5+ 、Th(OH) 3 + ,Th 4 (OH) 12 4+ etc.), thereby affecting the metal organic framework composite material loaded with nano-silica of the present application to metal ions, such as Th 4+ In addition, in the spent fuel reprocessing process, the acidity of the liquid to be treated containing radioactive metal ions is relatively high, usually reaching the molar nitric acid level. Under high acidity, metal ions, such as thorium ions, exist in the form of pure thorium ions, so that the metal organic framework composite material loaded with nano-silica of the present application adsorbs metal ions in an environment with a pH of less than or equal to 3, which is conducive to simplifying the treatment steps of adsorbing radioactive metal ions. In some preferred embodiments, the pH of the liquid to be treated containing high-valent metal ions is 2-3, and more preferably 3.
[0039] In some embodiments, the concentration of the high-valent metal ions in the liquid to be treated containing high-valent metal ions is 15 mg / L-300 mg / L. By making the concentration of the high-valent metal ions in the liquid to be treated within the above range, it is beneficial to achieve a good adsorption effect. Exemplarily, the concentration of the high-valent metal ions in the liquid to be treated containing high-valent metal ions can be 15 mg / L, 30 mg / L, 45 mg / L, 60 mg / L, 85 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, 250 mg / L, 300 mg / L or a value between the ranges consisting of any two of them.
[0040] In some embodiments, the adsorption conditions include: a temperature of 25-30°C; an oscillation rate of 200r / min-220r / min; and an oscillation time of 5-8h. Setting the above adsorption conditions is conducive to the full combination of the liquid to be treated containing high-valent metal ions and the metal organic framework composite material loaded with nano-silica, thereby improving the adsorption effect of the composite material.
[0041] The third aspect of the present invention provides a method for preparing a metal organic framework composite material loaded with nano-silicon dioxide, comprising uniformly dispersing nano-silicon dioxide, a metal precursor, an organic ligand, N,N-dimethylformamide (DMF), deionized water and an acetic acid solution to obtain a reaction solution, subjecting the reaction solution to a hydrothermal reaction at 140°C-160°C for 8h-12h, filtering and collecting a solid product, and drying the solid product to obtain the metal organic framework composite material loaded with nano-silicon dioxide; the metal precursor is zirconium (IV) oxychloride octahydrate; and the organic ligand is ellagic acid. The method of the present invention can obtain a metal organic framework composite material loaded with nano-silicon dioxide by mixing the active component, the metal precursor and the organic ligand in one pot, and then performing a one-step hydrothermal reaction, and the method is simple and the raw material cost is low. In the method of the present invention, nano-silica is mixed with a metal-organic framework material, and the metal-organic framework material contains carbon-oxygen bonds, high oxygen bonds, free carboxyl groups and the like, and silica can be loaded on the metal-organic framework material through the combination between the bonds; and the loaded silica does not change the original structure of the metal-organic framework material, thus avoiding damage to the pore structure of the metal-organic framework material, thereby being beneficial to maintaining the adsorption sites of the composite material and improving the adsorption performance of the composite material.
[0042] In some embodiments, the active component nano-silicon dioxide and metal precursor are first added to NN-dimethylformamide (DMF) and dispersed evenly, and then the organic ligand, deionized water, and acetic acid solution are added in sequence and mixed evenly. The method of the present invention first disperses the nano-silicon dioxide and the metal precursor evenly in DMF, so that the nano-silicon dioxide is completely evenly dispersed in the solution, which is beneficial to improve the dispersibility of the nano-silicon dioxide on the metal organic framework material in the prepared metal organic framework composite material loaded with nano-silicon dioxide, thereby improving the adsorption performance of the composite material. The raw materials used in the preparation method of the present invention are low in cost, can be completed by a one-step hydrothermal reaction, and are simple to operate.
[0043] In the present invention, the dispersion can be carried out in a manner known to those skilled in the art, and the present invention does not specifically limit this. For example, it can be carried out by ultrasound, vibration, etc. The present invention does not specifically limit the dispersion time, as long as the material can be evenly dispersed. Exemplarily, the time for evenly dispersing the active component nano-silicon dioxide and the metal precursor in NN-dimethylformamide (DMF) can be 50 minutes.
[0044] In some embodiments, the mass ratio of the active component to the metal precursor is 0.03-0.08:1. By making the mass ratio of the active component to the metal precursor within the above range, it is beneficial to improve the ability of the prepared metal organic framework composite material loaded with nano-silica to adsorb metal ions. Exemplarily, the mass ratio of the active component to the metal precursor is 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1 or a ratio between the ranges consisting of any two ratios. In some preferred embodiments, the mass ratio of the active component to the metal precursor is 0.03-0.07:1.
[0045] In some embodiments, the molar ratio of the organic ligand to the metal precursor is 1.5 to 2.5:1. By making the molar ratio of the organic ligand to the metal precursor within the above range, it is beneficial for the reactants to react fully and effectively, and the crystal structure of the obtained composite material is better, which is beneficial to improve the chemical stability of the composite material. In some preferred embodiments, the molar ratio of the organic ligand to the metal precursor is 1.9 to 2.1:1. More preferably, the molar ratio of the organic ligand to the metal precursor is 2:1.
[0046] In some embodiments, the concentration of the acetic acid solution is 14 to 18 mol L -1 The acetic acid solution of the above concentration can act as a catalyst, which is beneficial to catalyze the hydrothermal reaction and improve the reaction yield. For example, the concentration of the acetic acid solution can be 14 mol L -1 , 14.5 mol L -1 , 15 mol L -1 , 15.5 mol L -1 , 16 mol L -1 , 16.5 mol L -1 , 17 mol L -1 , 17.5 mol L -1 , 18 mol L -1 or a value between any two of the ranges formed by the above values. In a preferred embodiment, the concentration of the acetic acid solution is 17.5 mol L -1 .
[0047] In some embodiments, the volume ratio of N,N-dimethylformamide, acetic acid solution and deionized water is (3-6): (2-4): (1-2). By making the volume ratio of N,N-dimethylformamide, acetic acid solution and deionized water within the above range, it is beneficial for the hydrothermal reaction to proceed fully, and the obtained composite material has a better crystal structure, thereby improving the thermal stability of the composite material. In a preferred embodiment, the volume ratio of N,N-dimethylformamide, acetic acid solution and deionized water is 4:3:2.
[0048] In some embodiments, the nano-silicon dioxide is a nano-powder with a particle size of 10-20 nm and a purity of 99.5% or more. Exemplarily, the metal impurities in the nano-silicon dioxide used in the present invention are at a trace level. The nano-silicon dioxide of the above specifications is relatively small in size, which is conducive to maintaining the pore structure of the metal organic framework material and reducing the blockage of the pore structure; in addition, it is also conducive to the uniform distribution of nano-silicon dioxide on the metal organic framework material, thereby improving the adsorption performance of the composite material.
[0049] In the present invention, the hydrothermal reaction can be carried out in a manner known to those skilled in the art, and the present invention does not impose any particular limitation thereto. In some embodiments, the hydrothermal reaction is carried out in an oil bath reflux heating manner.
[0050] In some embodiments, the drying temperature is 120-150°C and the time is 12-24h. The solid product prepared by drying the above-mentioned drying conditions is beneficial to maintain the adsorption activity of the prepared metal organic framework composite material loaded with nano-silica, and saves processing time. Exemplarily, the drying temperature can be 120°C, 130°C, 140°C, 150°C or a value between the ranges consisting of any two of them. Exemplarily, the drying time can be 12h, 14h, 16h, 18h, 20h, 22h, 24h or a value between the ranges consisting of any two of them.
[0051] In some embodiments, the preparation method further comprises repeatedly washing and filtering the filtered solid product with DMF and deionized water. Through the above washing and filtering operations, unreacted raw materials and organic solvents can be removed, thereby purifying the metal organic framework composite material loaded with nano-silica and improving its adsorption capacity.
[0052] The technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0053] Example
[0054] In the following examples, the organic and inorganic reagents whose concentrations are not mentioned are all commercially available analytically pure reagents.
[0055] Example 1
[0056] 0.05g of nano-silica was added to 100ml of DMF in which octahydrated zirconium (IV) dichloride (1.6g) was dissolved, and the mixture was ultrasonically treated for 50min to completely disperse the nano-silica in the solution. Then, 3g of ellagic acid, 50ml of deionized water, and 75ml of 17.5mol / L acetic acid solution were added to the mixed solution in sequence. The mixture was ultrasonically treated for 5min until the solution was evenly mixed and then transferred to a flask equipped with a condenser and heated in air at 140°C for 8h with stirring. After the reaction was completed, the reactor was gradually cooled to room temperature and the solid product was recovered by filtration. In order to remove the unreacted reactants, the solid product was stirred and dispersed in 4×50mL DMF at room temperature for 12h and then filtered out. The solid product was repeated three times. In order to further remove DMF, the same operation was repeated with 4×50mL of deionized water instead of DMF. Finally, the solid product was dried at 130°C overnight to obtain a metal organic framework composite material loaded with nano-silica, named: SU-102(Zr)@SiO 2 -1. In this disclosure, "@" indicates the structure of nano-silicon dioxide loaded on Zr-organic framework material. The sample was subjected to X-ray crystal diffraction test, and the test results are as follows Figure 1 shown.
[0057] Example 2
[0058] 0.1g of nano-silica was added to 100mL of N-N-dimethylformamide in which octahydrated zirconium (IV) dichloride (1.6g) was dissolved, and the mixture was ultrasonically treated for 50min to completely disperse the nano-silica in the solution. Then, 3g of ellagic acid, 50ml of deionized water, and 75ml of 17.5mol / L acetic acid solution were added to the mixed solution in sequence. The solution was ultrasonically treated for 5min until it was evenly mixed and then transferred to a flask equipped with a condenser and stirred and heated at 140°C in air for 8h. After the reaction was completed, the reactor was gradually cooled to room temperature and the solid product was recovered by filtration. In order to remove the unreacted reactants, the above solid product was stirred and dispersed in 4×50mL DMF at room temperature for 12h and then the solid product was filtered out, and the reaction was repeated three times. In order to further remove DMF, the same operation was repeated with 4×50mL of deionized water instead of DMF. Finally, the solid product was dried at 130°C overnight to obtain a metal organic framework composite material loaded with nano-silica, named: SU-102(Zr)@SiO 2 -2. The sample was subjected to X-ray crystal diffraction test, and the test results were as follows Figure 2 shown.
[0059] Comparative Example 1
[0060] Zirconium (IV) dichloride octahydrate (1.6 g) and ellagic acid (3 g) were added to a mixed solution of 100 ml DMF and 50 ml deionized water, and ultrasonicated for 10 minutes to make the solution fully mixed. Then 75 ml of acetic acid solution was added to the mixed solution, and ultrasonicated for 5 minutes until the solution was mixed evenly, and then transferred to a flask equipped with a condenser, and stirred and heated at 140 ° C in air for 8 hours. After the reaction was completed, the reactor was gradually cooled to room temperature, and the solid product was recovered by filtration. In order to remove the unreacted reactants, the above solid product was stirred and dispersed in 4×50 mL DMF at room temperature for 12 hours, and then the solid product was filtered out, and repeated three times. In order to further remove DMF, the same operation was repeated using 4×50 mL deionized water instead of DMF. Finally, the solid product was dried at 130 ° C overnight and named: SU-102 (Zr). The sample was subjected to X-ray crystal diffraction test, and the test results are as follows Figure 3 shown.
[0061] Comparative Example 2
[0062] 0.2g of nano-silica was added to 100ml of DMF in which octahydrated zirconium (IV) dichloride (1.6g) was dissolved, and the mixture was ultrasonically treated for 50min to completely disperse the nano-silica in the solution. Then, 3g of ellagic acid, 50ml of deionized water, and 75ml of 17.5mol / L acetic acid solution were added to the mixed solution in sequence. The solution was ultrasonically treated for 5min until the solution was evenly mixed and then transferred to a flask equipped with a condenser and heated in air at 140°C for 8h with stirring. After the reaction was completed, the reactor was gradually cooled to room temperature and the solid product was recovered by filtration. In order to remove the unreacted reactants, the solid product was dispersed in 4×50mL DMF at room temperature with stirring for 12h and then filtered out. The solid product was repeated three times. In order to further remove DMF, the same operation was repeated with 4×50mL of deionized water instead of DMF. Finally, the solid product was dried at 130°C overnight and named: SU-102(Zr)@SiO 2 The sample was subjected to X-ray crystal diffraction test, and the test results are as follows Figure 4 shown.
[0063] The nano-silica loaded metal organic framework composite materials prepared in the above Examples 1-2 and Comparative Examples 1-2 were used as adsorbents to test the thorium ion adsorption effect.
[0064] Test method for thorium ion adsorption effect:
[0065] A thorium solution with a concentration of about 100 mg / L was prepared, the pH of the thorium solution was adjusted to 3, and the precise concentration C of the thorium solution before adsorption was measured by ICP-MS. 0. Then, 10 mL of thorium solution with a pH of 3 and 2 mg of the metal organic framework composite material loaded with nano-silica of Example 1-3 and Comparative Example 1-2 were added to 50 ml centrifuge tubes respectively, sealed and placed in a constant temperature water bath oscillating box. The adsorption conditions were set as follows: temperature 25°C, oscillation time 5 h. After the adsorption was completed, the centrifuge tube was taken out, separated with a syringe with a filter head, and the supernatant was taken. The concentration of thorium ions in each centrifuge tube was measured by ICP-MS. i , the adsorption capacity Q of the adsorbents of Examples 1-3 and Comparative Examples 1-2 is calculated according to formula (1): e ,
[0066] Q e =(C 0 -C i )×V / m (1),
[0067] Where C0 is the initial concentration of thorium ions in the thorium solution before adsorption, Ci is the concentration of thorium ions in the thorium solution after adsorption, V represents the volume of the adsorption mother solution, and m represents the mass of the adsorbent.
[0068] The test results are recorded in Table 1.
[0069] Table 1
[0070]
[0071] From the above test results, it can be seen that the composite material of the present application with a nano-silica loading in the range of 1.2%-3.0% has better adsorption performance than the unloaded metal organic framework material (Comparative Example 1). Compared with the composite material of Comparative Example 2 with a higher nano-silica loading, the composite material of the present application has better adsorption performance.
[0072] Examples 3-6 and Comparative Examples 3-4
[0073] The materials prepared in Example 1-2 and Comparative Example 1-2 were used as adsorbents, and the adsorption effect of thorium ions was tested under different pH conditions according to the above method. The results are shown in Table 2.
[0074] Table 2
[0075]
[0076] It can be seen from the above test results that compared with the MOF material without nano-silica loading, the metal-organic framework composite material loaded with nano-silica in the present application has better adsorption performance at a lower pH.
[0077] Example 7
[0078] Standard adsorption curve for thorium ions
[0079] Thorium solutions with concentrations of approximately 15, 50, 100, 250, and 300 mg / L were prepared in sequence. The pH of the thorium solution was adjusted to 3, and the precise concentration of the thorium solution before adsorption was measured by ICP-MS. 0 Then, 10 mL of thorium solution with different concentrations and 2 mg of adsorbent SU-102(Zr)@SiO were taken in turn. 2 -2 were added to 50ml centrifuge tubes, sealed and placed in a constant temperature water bath oscillator. The adsorption conditions were set as follows: temperature 25°C, oscillation time 5h. After the adsorption was completed, the centrifuge tube was taken out, separated with a syringe with a filter head, and the supernatant was taken, and its concentration C was measured by ICP-MS i According to the above formula (1), the adsorption capacity of SU-102(Zr)@SiO was calculated and the 2 The standard adsorption curve of thorium ions by -2 adsorbent is shown in Figure 5 .
[0080] from Figure 4 The results show that the adsorption capacity of SU-102(Zr)@SiO2-2 increases with the increase of the initial concentration of thorium, and the maximum adsorption capacity reaches 118.1 mg / g under the environment of pH=3.
[0081] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A metal organic framework composite material loaded with nano-silicon dioxide, characterized in that: The metal organic framework composite material loaded with nano-silicon dioxide comprises a zirconium-organic framework material and an active component; The active component includes nano silicon dioxide; The organic ligand of the zirconium-organic framework material is ellagic acid.
2. The composite material according to claim 1, characterized in that Based on the total weight of the metal organic framework composite material loaded with nano silicon dioxide, the mass fraction of the nano silicon dioxide active component is 1.2%-3.0%.
3. The metal organic framework composite material loaded with nano-silicon dioxide according to claim 1 or 2, characterized in that: Based on the total weight of the zirconium-organic framework material, the content of the organic ligand is 60%-68%.
4. Use of a nano-silica loaded metal organic framework composite material according to any one of claims 1 to 3 in adsorbing high-valent metal ions, wherein: The high-valent metal ion is selected from metal ions with a valence of +4 or above; preferably, the high-valent metal ion is a thorium ion.
5. The use according to claim 4, characterized in that The method comprises the following steps: mixing the metal organic framework composite material loaded with nano-silicon dioxide with a liquid to be treated containing high-valent metal ions; wherein: The pH of the liquid to be treated containing high-valent metal ions is less than or equal to 3; The concentration of the high-valent metal ions in the liquid to be treated containing the high-valent metal ions is 15 mg / L-300 mg / L; and / or The adsorption conditions include: temperature of 25-30°C; oscillation rate of 200r / min-220r / min; and oscillation time of 5-8h.
6. A method for preparing a metal organic framework composite material loaded with nano-silicon dioxide, characterized in that: The method comprises uniformly dispersing nano silicon dioxide, a metal precursor, an organic ligand, N,N-dimethylformamide, deionized water and an acetic acid solution to obtain a reaction solution. The reaction solution is subjected to a hydrothermal reaction at 140° C. to 160° C. for 8 h to 10 h, the precipitate is collected by filtration, and the precipitate is dried to obtain the metal-organic framework composite material loaded with nano-silica; The metal precursor is zirconium (IV) oxychloride octahydrate; and the organic ligand is ellagic acid.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the nano silicon dioxide to the metal precursor is 0.03-0.08:
1.
8. The preparation method according to claim 6 or 7, characterized in that: The molar ratio of the organic ligand to the metal precursor is 1.5 to 2.5:1; preferably, the molar ratio of the organic ligand to the metal precursor is 1.9 to 2.1:
1.
9. The preparation method according to claim 6 or 7, characterized in that: The concentration of the acetic acid solution is 14-18 molL -1 ; Further preferably, the volume ratio of N,N-dimethylformamide, acetic acid solution and deionized water is (3-6):(2-4):(1-2); preferably (4-5):(2.5-3.5):(1.5-2).
10. The preparation method according to claim 6 or 7, characterized in that: The nano silicon dioxide is nano powder with a particle size of 10-20nm and a purity of more than 99.5%.